Curcuma longa and Boswellia serrata for Improving Functional Status in Osteoarthritis Patients: From Bench to Bedside Evidences - Pinzon, Rizaldy Taslim; Wijaya, Vincent Ongko (Asian Journal of Medical Sciences, 2019)
Background: The management of osteoarthritis (OA) represents a real challenge. Curcumin is a highly pleiotropic molecule with an excellent safety profile.Some previous studies showed the extract of Curcuma longa and Boswellia Serrata(CB extract) is a promising potential as therapeutic interventions against OA. Aims and Objective: This study aimed to measure the effectiveness and safety of CB extract for improving functional status in patients with OA. Materials and Methods: A randomized controlled trial (RCT) in OA patients. The treatment used in this trial were CB extract (350 mg of Curcuma longa and 150 mg Boswellia Serrata) and NSAID (400 mg ibuprofen or 50 mg diclofenac sodium). Subjects were randomized to 3 different group (Group 1: CB extract and NSAID; group 2: CB extract; group 3: NSAID). Each subject would be followed up 3 times: baseline (visit I), 2 weeks after baseline (visit II), and 4 weeks after baseline (visit III). The measurement of functional status with WOMAC (Western Ontario and McMaster Universities Osteoarthitis Index). Results: There were 105 osteoarthritis patients. Seven subjects were lost to follow up and three subjects were excluded from the study due to medication side effect. Ninety-five subjects (group 1: 36; group 2: 29, group 3: 30) remained for complete analysis. Delta (Δ) WOMAC score defined as the result of subtraction between WOMAC score at visit I and WOMAC score at visit III. Group 1 showed the greatest reduction of WOMAC score after 4 weeks of treatment (ΔWOMAC = 12.08 ± 18.6). Group 3 has the least WOMAC score reduction (ΔWOMAC = 6.9 ± 16). There was no statistically different of ΔWOMAC score between groups (p = 0.367). There were no statistically different of the prevalence of AE between groups at the visit II (p: 0.119) and at the visit III (p: 0.767). Conclusion: CB extract is effective and safe for improving functional status in OA patients.